A Theil Decomposition of Regional Grouping in Indonesia’s Human Development Index - Rah Adi Fahmi Ginanjar; Hady Sutjipto; Indra Suhendra; Cep Jandi Anwar (Economics Development Analysis Journal, 2024)
This research is designed to investigate regional differences in human development in Indonesia based on the Human Development Index (HDI) as a main indicator. With the use of the Theil Index decomposition method, this paper investigates the intra- and inter-regional disparities in Java vs. outside Java and KBI vs. KTI (Western Indonesia-Eastern Indonesia). Furthermore, the study uses convergence models (σ- and β-convergence) to examine the speed at which zones with lower HDI access regions with higher HDI. The dataset employed in the study was data from various competencies at each regency-cities in Indonesia during its period of 2010-2021, which was publicly available at the Indonesian Central Bureau of Statistics (BPS). The findings show a significant decrease in human development disparities over time, although the convergence process remains slow. Intra-regional inequality contributes more significantly to the overall disparity than inter-regional inequality, particularly within the KBI-KTI dichotomy. This study suggests that while Indonesia is on a path toward reducing regional disparities, more targeted policy interventions are needed to accelerate the convergence process, particularly in underdeveloped regions like Eastern Indonesia.